Holistic Care for Persons with Post-Traumatic Stress Disorder (PTSD): Lesson Learned from Cave Rescue of Moo Pa Academy Mae Sai Soccer Team in Chiang Rai - ผดุงยาม มุกข์ดา; ทรัพย์ประเสริฐ วาสนา; ชนะกุล ปณตพร (Journal of The Royal Thai Army Nurses, 2019)
Moo Pa (Wild Boar) Academy Mae Sai is the name of the soccer team in Mae Sai district of Chiang Rai. After 12 members of the team and their coach went into Tham Luang-Khun Nam Nang Non cave and were trapped in the flooded cave for 17 days, they were at risk of having post-traumatic stress disorder (PTSD), a mental disorder that often surges after a person experiences or witnesses a terrifying event. Symptoms may include flashbacks, nightmares and severe anxiety, as well as uncontrollable thoughts about the event. When thinking about that event, there will be fear. Persons will try to avoid facing any event-related emotion, their mind being affected in a negative way, and they will have lower efficiency in performing routine tasks. If confronted with the triggering event, they might even show violent retaliatory behavior. In all cases, first phase of treatment will focus on physical assistance, in order for the persons to survive and avoid physical harm. Surviving or being safe will bring psychological support. From there, effective care treatment is required to reach a holistic restoration of persons including physical, mental, social and spiritual. Psychotherapy or counseling will help victims to realize and understand themselves. It is to say, to understand the negative effects that arise from their own thoughts, emotions and feelings towards the event. Patients will then have to change their perspective and link to their life energy, and develop spiritual health, which will result in inner peace and happiness. If the victims get proper care, they will be able to rehabilitate themselves, getting back to the normal balance in life. All lesson learned from the operation to rescue of Moo Pa Academy Mae Sai Soccer Team at Tham Luang cave in Chiang Rai is a good experience and learning model for society.